BRCA1 in the DNA damage response and at telomeres - Rosen, Eliot M. (Frontiers in Genetics, 2013)
Abstract. Mutations of the breast and ovarian cancer susceptibility gene 1 (BRCA1) account for about 40-45% of hereditary breast cancer cases. Moreover, a significant fraction of sporadic (non-hereditary) breast and ovarian cancers exhibit reduced or absent expression of the BRCA1 protein, suggesting an additional role for BRCA1 in sporadic cancers. BRCA1 follows the classic pattern of a highly penetrant Knudsen-type tumor suppressor gene in which one allele is inactivated through a germ-line mutation and the other is mutated or deleted within the tumor. BRCA1 is a multi-functional protein but it is not fully understood which function(s) is (are) most important for tumor suppression, nor is it clear why BRCA1 mutations confer a high risk for breast and ovarian cancers and not a broad spectrum of tumor types. Here, we will review BRCA1 functions in the DNA damage response (DDR), which are likely to contribute to tumor suppression. In the process, we will highlight some of the controversies and unresolved issues in the field. We will also describe a recently identified and under-investigated role for BRCA1 in the regulation of telomeres and the implications of this role in the DDR and cancer suppression.